Standardised Mortality Ratios in Homeless Populations in Dublin. - Ivers, Jo-Hanna (Dublin Regional Homeless Executive and Health Service Executive. Dublin., 2018)
Three hundred and forty three homeless people were verified as having died in the Dublin region between 2005 and 2015. More than three quarters were male (n=263/76.7%). However, due to probable incompleteness of recording of deaths in the homeless population, the number presented is a minimum number of known deaths within the population. This is particularly relevant to deaths occurring prior to the introduction of the Pathway Accommodation and Support System recording system in 2011. The median age at death of a homeless person in the Dublin Region over this period was 42 years old. The median age at death of homeless women in the current study is 37 years old. The median age at death of homeless men in the current study is 44 years old. Recognising that the current data represents a minimum is imperative. Homelessness is a serious public health concern.The standardised mortality ratios (SMRs) are calculated for the years in which a denominator is available (i.e. the number of all people accessing DRHE accommodation in a given year). Thus SMRs for 2011, 2012, 2013, 2014 and 2015 for male and female homeless persons have been calculated in this study. This study found the SMR for homeless men was between 3 and almost 10 times higher compared to Dublin males in the general population. The SMR for homeless women was 6 to 10 times higher than Dublin women in the general population.Cause of death was also examined utilising death certificates and coroner’s records. Drug and alcohol intoxication was the most common cause of death amongst the homeless population, accounting for 39.9% of deaths where cause of death is known. Homeless persons in the current study were more likely to die by overdose than the general population, with opioids accounting for the majority of drug related deaths. Both the Coroner’s Office and the hospices have an important consultative role to play in the recording and reporting of homeless deaths and any proposed reform should include both as key stakeholders; others include addiction services, mental health services, prison services and hospitals.
Keywords: Standardised Mortality Ratios (SMRs); Homeless; Health; Ageing; Inclusive Society; Epidemiology; Chronic Health Condition